Desulfurization, denitration and dust removal process for low-sulfur flue gas
By modifying porous high-iron ash and modified activated carbon as desulfurization and denitrification adsorbents, the problem of low adsorption efficiency in the prior art is solved, efficient desulfurization and denitrification effect is achieved, and sulfur capacity and specific surface area are improved.
Patent Information
- Application Number
- CN202411592625.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, in the gas desulfurization and denitrification adsorbent, gas molecules do not easily diffuse and adsorption on the particle surface, resulting in low adsorption efficiency, and sulfur capacity, nitrate capacity and specific surface area need to be improved.
Modified porous high-iron ash and modified activated carbon are used as desulfurization and denitrification adsorbents. The pore structure and specific surface area of the adsorbent are improved through NaClO modification method and sodium hydroxide activation treatment to form an efficient adsorbent bed.
It significantly improves the desulfurization and denitrification efficiency, increases the sulfur capacity and nitrate capacity of the adsorbent, increases the specific surface area, improves the diffusion and adsorption capacity of gas molecules, and reduces pollutant emissions.
Smart Images

Figure BDA0005125978520000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of desulfurization and denitrification, and in particular to a desulfurization, denitrification and dust removal process for low-sulfur flue gas. Background Art
[0002] The development and utilization of coal resources produces a large amount of gas pollution, which harms the ecological environment. With the vigorous development of industrial production, the combustion of fossil fuels has become one of the main sources of air pollution, especially the emission of sulfur dioxide (SO2) and nitrogen oxides (NOx), which not only causes environmental problems such as acid rain and photochemical smog, but also poses a serious threat to human health. Therefore, desulfurization and denitrification technology came into being and became one of the important means to control air pollution and protect the ecological environment.
[0003] Fly ash is a small spherical or irregular particle formed by the surface tension of the unburned coal powder and ash in the high-temperature flue gas of the power plant. It has volcanic ash activity and adsorption characteristics. This characteristic of fly ash enables it to assist the calcium-based desulfurizer in adsorbing and absorbing a part of sulfur oxides in flue gas desulfurization; however, the specific surface area of the fly ash adsorbent is small. When the fly ash adsorbent is used for desulfurization and denitrification, the gas molecules are not easy to diffuse and adsorb on the surface of the particles, and it is difficult to achieve effective adsorption of sulfides and nitrides in the gas. Moreover, simply using the adsorption characteristics of fly ash and using it for flue gas desulfurization and denitrification is also likely to lead to low overall adsorption efficiency. The sulfur capacity, nitrate capacity, specific surface area and desulfurization and denitrification efficiency of desulfurization and denitrification need to be further improved;
[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a desulfurization, denitrification and dust removal process for low-sulfur flue gas, which is used to solve the technical problems in the prior art that the gas molecules are not easy to diffuse and adsorb on the particle surface of the combined desulfurization and denitrification adsorbent in the gas desulfurization project, and the specific surface area and desulfurization and denitrification efficiency of the combined desulfurization and denitrification agent need to be further improved.
[0006] The object of the present invention can be achieved by the following technical solution: A desulfurization, denitrification and dust removal process for low-sulfur flue gas, comprising the following steps:
[0007] S1. After the low-sulfur flue gas passes through the dust collector to filter out mechanical dust in the gas, the temperature is reduced to room temperature to obtain pre-treated exhaust gas;
[0008] S2. The desulfurization and denitration adsorbent filler is loaded inside the desulfurization and denitration tower to form an adsorbent bed in the desulfurization and denitration tower. The temperature of the desulfurization and denitration tower is increased to 120-160°C. The pre-treated exhaust gas passes through the adsorbent bed of the desulfurization and denitration adsorbent from bottom to top and is discharged from the top of the desulfurization and denitration tower.
[0009] S3. The desulfurization and denitrification slag in the desulfurization and denitrification tower is discharged from the bottom of the desulfurization and denitrification tower, and is crushed into powder to obtain a by-product.
[0010] Furthermore, the desulfurization and denitrification adsorbent is prepared by granulating a mixed mucus composed of modified porous high iron ash, modified activated carbon, and colloidal suspension in a weight ratio of 2-4:1-3:3-5.
[0011] Furthermore, the granulation method is: the mixed mucus is granulated by a disc ball forming machine and then placed in a muffle furnace, the temperature of the muffle furnace is increased to 450-500°C, and the mixture is kept warm and roasted for 2-3 hours to obtain a desulfurization and denitrification adsorbent, the ball forming machine speed is 25r / min, and the granulation diameter is 8-12mm.
[0012] Furthermore, the modified porous high iron ash is obtained by processing the following steps:
[0013] A1. Add the fly ash crushed by ball mill and deionized water into a permanent magnetic wet separator for magnetic separation, and dry it in a drying oven at a temperature of 90-95° C. for 10-12 hours to obtain high iron ash;
[0014] A2. Put high iron ash, calcium oxide and deionized water into a water bath, stir and filter, and put the filter cake into a vacuum drying oven at a temperature of 100-110°C for 10-12 hours to obtain high iron ash aggregate;
[0015] A3. Add high iron ash aggregate and colloidal suspension into a reaction kettle, stir until slurry, place into a muffle furnace, raise the temperature of the muffle furnace to 360-380°C, keep warm and roast for 2-3h to obtain porous high iron ash;
[0016] A4. Place the porous high iron ash and the modified solution into a cold water bath and stir, wash with deionized water until neutral, filter, and dry the filter cake in an empty drying oven at a temperature of 85-95°C to constant weight to obtain modified porous high iron ash.
[0017] Among them, the synthetic reaction mechanism of modified porous high iron ash is:
[0018] The pore structure of the modified porous high iron ash adsorbent obtained by the NaClO modification method promotes the formation of the active component K2FeO4. The high-valent iron K2FeO4 is the main active component on the adsorbent surface. Fe(VI) has strong oxidizing properties and provides oxidation sites on the surface of the porous high iron ash modified by sodium hypochlorite, promoting the oxidation reaction of sulfides and nitrides. Finally, Fe(VI) is reduced to Fe(III) and SO2 is oxidized to SO4. 2+ , nitrogen oxides are oxidized to NO 3- , and then with Ca 2+ , K + After the cations bind, they are removed.
[0019] Furthermore, in step A1, the fly ash and deionized water usage ratio is 100 g:20 mL, the ball mill speed is 500 r / min, the ball milling time is 4 h, and the permanent magnet magnetic field strength is 12000 GS.
[0020] Furthermore, in step A2, the water bath temperature is 85-95° C., the stirring time is 3-5 h, and the dosage ratio of high iron ash, calcium oxide, and deionized water is 3-5 g: 1-2 g: 250-270 mL.
[0021] Furthermore, the colloidal suspension in step A3 is composed of sawdust pore-forming agent, sodium-based bentonite binder, and deionized water in a dosage ratio of 5-10g:30-40g:5-10mL, and the dosage ratio of iron ash aggregate and colloidal suspension is 40-50g:100-150mL.
[0022] Furthermore, the modified solution in step A4 is composed of potassium hydroxide, sodium hypochlorite and deionized water in a ratio of 25-30g:10-15g:100-120mL, and the porous high iron ash and modified solution in a ratio of 10-12g:20-40mL.
[0023] Furthermore, the modified activated carbon is obtained by processing the following steps:
[0024] B1. Wash the coconut shell activated carbon with deionized water until it is neutral, dry it in a vacuum drying oven at a temperature of 100-110° C. to constant weight, and grind and screen 100-120 mesh activated carbon to obtain pretreated activated carbon;
[0025] B2. Add the pretreated activated carbon and sodium hydroxide powder into a nickel boat, place the nickel boat into a nitrogen-protected tubular furnace, increase the temperature to 500-600° C., keep the temperature for 40-70 min, and obtain modified activated carbon by post-treatment.
[0026] Furthermore, in step B2, the ratio of activated carbon to sodium hydroxide is 1g:1-5g, the flow rate of the tubular furnace is 200mL / min, and the heating rate is 5°C / min; post-treatment includes: cooling after the reaction is completed, adding hydrochloric acid to adjust the pH of the system to 5, maintaining for 30 minutes, washing with deionized water, filtering, and drying the filter cake in a vacuum drying oven at a temperature of 100-110°C to constant weight to obtain modified activated carbon.
[0027] Among them, the synthetic reaction mechanism of modified activated carbon is:
[0028] The activated carbon was activated with sodium hydroxide, which increased the oxygen content of the modified activated carbon, reduced the content of alkaline functional groups in the surface functional groups, and increased the content of acidic functional groups, especially the significant increase of carboxyl and lactone groups. The increase of lactone groups is beneficial to the improvement of the catalytic performance of activated carbon. The modified activated carbon has more developed pores, significantly increased specific surface area, significantly increased mesopores, and reduced micropore content. Its average pore volume also increased. The modified activated carbon was activated by alkali dissolution method to obtain ultra-high specific surface area activated carbon containing a large number of micropores. The specific surface area of the activated carbon reached 2885m 2 / g of super activated carbon.
[0029] The present invention has the following beneficial effects:
[0030] 1. The present invention utilizes the pore structure of the modified porous high iron ash adsorbent obtained by the NaClO modification method to promote the generation of the active component K2FeO4. The high-valent iron K2FeO4 is the main active component on the adsorbent surface. Fe(VI) has strong oxidizing properties and provides oxidation sites on the surface of the sodium hypochlorite modified porous high iron ash to promote the oxidation reaction of sulfides and nitrides. Finally, Fe(VI) is reduced to Fe(III) and SO2 is oxidized to SO4. 2+ , the nitride is oxidized to NO 3- , and then with Ca 2+ , K + After the cations combine, the sulfides and nitrides are removed, thereby reducing the pollutant emissions in the sintering flue gas.
[0031] 2. The present invention also utilizes sodium hydroxide to activate the activated carbon, so that the oxygen content of the modified activated carbon increases, the content of alkaline functional groups in the surface functional groups decreases, and the content of acidic functional groups increases, especially the carboxyl and lactone groups increase significantly, and the increase of lactone groups is beneficial to the improvement of the catalytic performance of the activated carbon. After the modification, the pores of the activated carbon are more developed, the specific surface area is significantly increased, the mesopores increase significantly, and the micropore content decreases, and the average pore volume also increases. The modified activated carbon is activated by alkali dissolution method to obtain super activated carbon with ultra-high specific surface area containing a large number of micropores, which effectively improves the pore volume and specific surface area of the combined desulfurization and denitrification adsorbent.
[0032] 3. The present invention also uses a combined desulfurization and denitrification adsorbent for desulfurization and denitrification. The increase in the concentration of nitrogen oxides will promote the desulfurization performance of the combined desulfurization and denitrification adsorbent, because SO2 will react with the active substance Fe (VI), and the presence of nitrogen oxides will promote the forward reaction. The nitrogen oxides in the low-sulfur flue gas help to improve the ability of the combined desulfurization and denitrification adsorbent to remove SO2. SO2 can react with NO and CaO to generate the intermediate product NO3SO3Ca, and then further converted into CaSO4. Nitrogen oxides will not compete with sulfides, but will promote the forward desulfurization reaction, thereby improving the desulfurization and denitrification efficiency.
[0033] 4. The desulfurization by-products of the present invention can be comprehensively utilized and processed, which can not only prevent secondary pollution, but also increase the income of power plants and reduce operating costs. The desulfurization ash can be used as an anti-seepage layer of landfills, embankment filling, land backfill, road construction, and an additive for cement production. It can also be used as an admixture for concrete to manufacture concrete bricks and silica-lime bricks. The application of acidic desulfurization by-products has a slight acidifying effect on the soil and can improve soil and crop nutrients. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment provides a method for preparing a desulfurization and denitrification adsorbent filler for desulfurization, denitrification and dust removal of low-sulfur flue gas, comprising the following steps:
[0037] S1. Preparation of high iron ash
[0038] The fly ash is ball-milled to obtain fly ash powder;
[0039] Weigh: 100 g of fly ash powder and 20 mL of deionized water, add them into a permanent magnetic wet separator for magnetic separation, put them into a drying oven at 90° C. and dry them for 10 hours. The ball mill speed is 500 r / min, the ball milling time is 4 hours, and the magnetic field strength of the permanent magnet is 12000 GS.
[0040] S2. Preparation of high iron ash aggregate
[0041] Weigh: 300g of high iron ash, 10g of calcium oxide, and 25000mL of deionized water, put them into a water bath, stir, filter, and dry the filter cake in a vacuum drying oven at 90°C for 10h. The water bath temperature is 85°C and the stirring time is 3h.
[0042] S3. Preparation of porous high iron ash
[0043] The sawdust pore former, sodium bentonite binder and deionized water were mixed uniformly in a dosage ratio of 5 g:30 g:10 mL to obtain a colloidal suspension;
[0044] Weigh: 400 g of iron ash aggregate and 1000 mL of colloidal suspension, add into the reactor, stir until slurry, place into the muffle furnace, increase the temperature of the muffle furnace to 400° C., and keep warm for 2 h.
[0045] S4. Preparation of modified porous high iron ash
[0046] Potassium hydroxide, sodium hypochlorite and deionized water were mixed uniformly in a dosage ratio of 25 g:10 g:100 mL to obtain a modified solution;
[0047] Weigh: 100 g of porous high iron ash and 200 mL of modified solution, add into a cold water bath and stir for 1 h, wash with deionized water until neutral, filter, and dry the filter cake in a drying oven at 85°C to constant weight to obtain modified porous high iron ash.
[0048] S5. Preparation of modified activated carbon
[0049] The coconut shell activated carbon was washed with deionized water until neutral, placed in a vacuum drying oven at 100°C and dried to constant weight, and ground and screened to obtain 100 mesh activated carbon to obtain pretreated activated carbon;
[0050] Weigh: 100 g of pretreated activated carbon and 100 g of sodium hydroxide powder, put them into a nitrogen-protected tubular furnace, cool them after the reaction is completed, add hydrochloric acid to adjust the pH of the system to 5, keep it for 30 minutes, wash with deionized water, filter, and dry the filter cake in a vacuum drying oven at 100°C to constant weight. The temperature of the tubular cremation furnace is 500°C, and the insulation time is 40 minutes.
[0051] S6. Preparation of desulfurization and denitrification adsorbent
[0052] Weigh: 200g of modified porous high iron ash, 10g of modified activated carbon, and 300mL of colloidal suspension, mix them, granulate them through a disc ball forming machine, and place them in a muffle furnace. The temperature of the muffle furnace is raised to 400°C, and the mixture is kept warm for 2h. The speed of the ball forming machine is 25r / min, and the granulation diameter is 8-12mm to obtain a desulfurization and denitrification adsorbent.
[0053] Example 2
[0054] This embodiment provides a method for preparing a desulfurization and denitrification adsorbent filler for desulfurization, denitrification and dust removal of low-sulfur flue gas, comprising the following steps:
[0055] S1. Preparation of high iron ash
[0056] The fly ash is ball-milled to obtain fly ash powder;
[0057] Weigh: 100 g of fly ash powder and 20 mL of deionized water, add them into a permanent magnetic wet separator for magnetic separation, put them into a drying oven at 93° C. and dry them for 11 hours. The ball mill speed is 500 r / min, the ball milling time is 4 hours, and the magnetic field strength of the permanent magnet is 12000 GS.
[0058] S2. Preparation of high iron ash aggregate
[0059] Weigh: 400g of high iron ash, 150g of calcium oxide, and 26000mL of deionized water, put them into a water bath, stir, filter, and dry the filter cake in a vacuum drying oven at 100°C for 11h. The water bath temperature is 90°C and the stirring time is 4h.
[0060] S3. Preparation of porous high iron ash
[0061] The sawdust pore-forming agent, sodium bentonite binder, and deionized water were mixed uniformly in a dosage ratio of 8 g:35 g:30 mL to obtain a colloidal suspension;
[0062] Weigh: 450 g of iron ash aggregate and 1200 mL of colloidal suspension, add into the reactor, stir until slurry, place into the muffle furnace, increase the temperature of the muffle furnace to 500° C., and keep warm for 3 hours.
[0063] S4. Preparation of modified porous high iron ash
[0064] Potassium hydroxide, sodium hypochlorite and deionized water were mixed uniformly in a dosage ratio of 27 g:13 g:110 mL to obtain a modified solution;
[0065] Weigh: 110 g of porous high iron ash and 300 mL of modified solution, add into a cold water bath and stir for 1.5 h, wash with deionized water until neutral, filter, and dry the filter cake in a drying oven at 90° C. to constant weight to obtain modified porous high iron ash.
[0066] S5. Preparation of modified activated carbon
[0067] The coconut shell activated carbon was washed with deionized water until neutral, placed in a vacuum drying oven at a temperature of 105°C and dried to constant weight, and ground and screened with 110 mesh activated carbon to obtain pretreated activated carbon;
[0068] Weigh: 100g of pretreated activated carbon and 250g of sodium hydroxide powder are loaded into a nitrogen-protected tubular furnace. After the reaction is completed, cool it, add hydrochloric acid to adjust the pH of the system to 5, maintain it for 30 minutes, wash it with deionizer, filter it, and dry the filter cake in a vacuum drying oven at a temperature of 105°C to constant weight. The temperature of the tubular cremation furnace is 550°C, and the insulation time is 55 minutes.
[0069] S6. Preparation of desulfurization and denitrification adsorbent
[0070] Weigh: 300g of modified porous high iron ash, 20g of modified activated carbon, and 400mL of colloidal suspension, mix them, granulate them in a disc-type ball-forming machine, and place them in a muffle furnace. The temperature of the muffle furnace is raised to 450°C, and the temperature is kept and roasted for 2.5h. The speed of the ball-forming machine is 25r / min to obtain a desulfurization and denitrification adsorbent. The granulation diameter is 8-12mm.
[0071] Example 3
[0072] This embodiment provides a method for preparing a desulfurization and denitrification adsorbent filler for desulfurization, denitrification and dust removal of low-sulfur flue gas, comprising the following steps:
[0073] S1. Preparation of high iron ash
[0074] The fly ash is ball-milled to obtain fly ash powder;
[0075] Weigh: 100 g of fly ash powder and 20 mL of deionized water, add them into a permanent magnetic wet separator for magnetic separation, put them into a drying oven at 95° C. and dry them for 12 hours. The ball mill speed is 500 r / min, the ball milling time is 4 hours, and the magnetic field strength of the permanent magnet is 12000 GS.
[0076] S2. Preparation of high iron ash aggregate
[0077] Weigh: 500g high iron ash, 20g calcium oxide, 27000mL deionized water, put into a water bath, stir, filter, and dry the filter cake in a vacuum drying oven at 110°C for 12h. The water bath temperature is 95°C and the stirring time is 5h.
[0078] S3. Preparation of porous high iron ash
[0079] The sawdust pore-forming agent, sodium bentonite binder, and deionized water were mixed uniformly in a dosage ratio of 10 g:40 g:50 mL to obtain a colloidal suspension;
[0080] Weigh: 500 g of iron ash aggregate and 1200 mL of colloidal suspension, add into the reactor, stir until slurry, place into the muffle furnace, increase the temperature of the muffle furnace to 600° C., and keep warm for 3 h.
[0081] S4. Preparation of modified porous high iron ash
[0082] Potassium hydroxide, sodium hypochlorite and deionized water were mixed uniformly in a dosage ratio of 30 g:15 g:120 mL to obtain a modified solution;
[0083] Weigh: 120 g of porous high iron ash and 400 mL of modified solution, add into a cold water bath and stir for 2 h, wash with deionized water until neutral, filter, and dry the filter cake in a drying oven at 95°C to constant weight to obtain modified porous high iron ash.
[0084] S5. Preparation of modified activated carbon
[0085] The coconut shell activated carbon was washed with deionized water until neutral, placed in a vacuum drying oven at 110°C and dried to constant weight, and ground and screened to obtain 120 mesh activated carbon to obtain pretreated activated carbon;
[0086] Weigh: 100g of pretreated activated carbon and 500g of sodium hydroxide powder are loaded into a nitrogen-protected tubular furnace, cooled after the reaction is completed, hydrochloric acid is added to adjust the pH of the system to 5, maintained for 30min, washed with deionized water, filtered, and the filter cake is placed in a vacuum drying oven at a temperature of 110°C and dried to constant weight. The temperature of the tubular cremation furnace is 600°C, and the insulation time is 70min.
[0087] S6. Preparation of desulfurization and denitrification adsorbent
[0088] Weigh: 400g of modified porous high iron ash, 30g of modified activated carbon, and 500mL of colloidal suspension, mix them, granulate them through a disc ball forming machine, and place them in a muffle furnace. The temperature of the muffle furnace is raised to 500°C, and the mixture is kept warm and calcined for 3h. The speed of the ball forming machine is 25r / min, and the granulation diameter is 8-12mm to obtain a desulfurization and denitrification adsorbent.
[0089] Example 4
[0090] This embodiment provides a desulfurization, denitrification and dust removal process for low-sulfur flue gas, comprising the following steps:
[0091] Step 1: After the low-sulfur flue gas passes through the dust collector to filter out mechanical dust in the gas, the temperature is reduced to room temperature to obtain pre-treated exhaust gas;
[0092] Step 2: Fill the desulfurization and denitration adsorbent filler prepared in Example 1 inside the desulfurization and denitration tower to form an adsorbent bed in the desulfurization and denitration tower. The temperature of the desulfurization and denitration tower is increased to 120° C. The pre-treated exhaust gas passes through the adsorbent bed of the desulfurization and denitration adsorbent from bottom to top and is discharged from the top of the desulfurization and denitration tower.
[0093] Step 3: The desulfurization and denitrification slag in the desulfurization and denitrification tower is discharged from the bottom of the desulfurization and denitrification tower, and is crushed into powder to obtain a by-product.
[0094] Example 5
[0095] This embodiment provides a desulfurization, denitrification and dust removal process for low-sulfur flue gas, comprising the following steps:
[0096] Step 1: After the low-sulfur flue gas passes through the dust collector to filter out mechanical dust in the gas, the temperature is reduced to room temperature to obtain pre-treated exhaust gas;
[0097] Step 2: Fill the desulfurization and denitration adsorbent filler prepared in Example 2 inside the desulfurization and denitration tower to form an adsorbent bed in the desulfurization and denitration tower. The temperature of the desulfurization and denitration tower is increased to 140° C. The pre-treated exhaust gas passes through the adsorbent bed of the desulfurization and denitration adsorbent from top to bottom and is discharged from the top of the desulfurization and denitration tower.
[0098] Step 3: The desulfurization and denitrification slag in the desulfurization and denitrification tower is discharged from the bottom of the desulfurization and denitrification tower, and is crushed into powder to obtain a by-product.
[0099] Example 6
[0100] This embodiment provides a desulfurization, denitrification and dust removal process for low-sulfur flue gas, comprising the following steps:
[0101] Step 1: After the low-sulfur flue gas passes through the dust collector to filter out mechanical dust in the gas, the temperature is reduced to room temperature to obtain pre-treated exhaust gas;
[0102] Step 2: Fill the desulfurization and denitration adsorbent filler prepared in Example 3 inside the desulfurization and denitration tower to form an adsorbent bed in the desulfurization and denitration tower. The temperature of the desulfurization and denitration tower is increased to 160° C. The pre-treated exhaust gas passes through the adsorbent bed of the desulfurization and denitration adsorbent from bottom to top and is discharged from the top of the desulfurization and denitration tower.
[0103] Step 3: The desulfurization and denitrification slag in the desulfurization and denitrification tower is discharged from the bottom of the desulfurization and denitrification tower, and is crushed into powder to obtain a by-product.
[0104] Comparative Example 1
[0105] The difference between this comparative example and Example 6 is that in the preparation process of the desulfurization and denitrification adsorbent filler used, in step S3, no colloidal suspension is added.
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 6 is that in the preparation process of the desulfurization and denitrification adsorbent filler used, in step S4, no modifying solution is added.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 6 is that in the preparation process of the desulfurization and denitrification adsorbent filler used, in step S5, no modified alkali solution is added.
[0110] Comparative Example 4
[0111] The difference between this comparative example and Example 6 is that in the preparation process of the desulfurization and denitrification adsorbent filler used, in step S5, no activated carbon is added.
[0112] Product performance test:
[0113] The sulfur capacity and nitrate capacity of the desulfurization and denitrification adsorbents used in Examples 4-6 and Comparative Examples 1-4 were determined with reference to the standard HG / T5031-2016 "Sulfur Capacity Test Method for Normal Temperature Activated Carbon Alkali Desulfurization Agent";
[0114] The specific surface areas of the desulfurization and denitrification adsorbents used in Examples 4-6 and Comparative Examples 1-4 were determined with reference to the standard GB / T21650.3-2011 "Mercury intrusion and gas adsorption method for pore size distribution and porosity of solid materials Part 3: Analysis of micropores by gas adsorption method";
[0115] The desulfurization efficiency of the desulfurization tanks for the mixed gas containing hydrogen sulfide in Examples 4-6 and Comparative Examples 1-4 was measured with reference to the standard GB / T21508-2008 "Method for testing the performance of coal-fired flue gas desulfurization equipment";
[0116] Adsorbent performance determination: refer to the formula S = (C0ηV × 10 3 T0) / G to determine the sulfur capacity of the desulfurization and denitrification adsorbent filler, refer to the formula: N = (C0ηV×10 3 T0) / G, determine the nitrate capacity of the desulfurization and denitrification adsorbent filler, where η = (C0-C) / C0×100%, η is the removal efficiency, T0 is the breakthrough time, S is the sulfur capacity and N is the nitrate capacity, C0 and C are the SO2 and NO concentrations at the reactor inlet and outlet, respectively, in mg / m 3 , V is the total flow rate of simulated flue gas, 1200mL / min, G is the mass of adsorbent, when the reactor outlet concentration is higher than the ultra-low emission standard requirement, that is, the SO2 concentration is higher than 35mg / m 3 (desulfurization efficiency is less than 93%), NO is higher than 50mg / m 3 When (denitrification efficiency is less than 50%), it is considered that the adsorbent has failed to penetrate, and the corresponding time is the penetration time T0. The specific test results are shown in Table 1 below.
[0117] Table 1-Performance test data of the sample
[0118]
[0119] Data Analysis:
[0120] Comparing and analyzing the data in Table 1 above, the desulfurization and denitration adsorbent prepared by the present invention has a sulfur capacity of 193.3 mg / g, a nitrate capacity of 754 mg / g, and a specific surface area of 472.2 m 2 / g, the desulfurization and denitrification efficiencies of the adsorbent reached 96.7% and 98% respectively; all performance test data were better than those of the comparative examples. The data showed that the present invention modified the porous high iron ash by alkali magnetic method, activated and modified it by alkali dissolution method to prepare activated carbon as the base material, added a binder and granulated it, which not only improved the sulfur capacity and specific surface area of the combined desulfurization and denitrification adsorbent, but also improved the desulfurization and denitrification efficiency.
[0121] The above are examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A desulfurization, denitrification and dust removal process for low-sulfur flue gas, characterized in that: The following steps are involved: S1. After the low-sulfur flue gas passes through the dust collector to filter out mechanical dust in the gas, the temperature is reduced to room temperature to obtain pre-treated exhaust gas; S2. The desulfurization and denitration adsorbent filler is loaded inside the desulfurization and denitration tower to form an adsorbent bed in the desulfurization and denitration tower. The temperature of the desulfurization and denitration tower is increased to 120-160°C. The pre-treated exhaust gas passes through the adsorbent bed of the desulfurization and denitration adsorbent from bottom to top and is discharged from the top of the desulfurization and denitration tower. S3. The desulfurization and denitrification slag in the desulfurization and denitrification tower is discharged from the bottom of the desulfurization and denitrification tower, and is crushed into powder to obtain a by-product.
2. A desulfurization, denitrification and dust removal process for low-sulfur flue gas according to claim 1, characterized in that: The desulfurization and denitrification adsorbent is prepared by granulating a mixed mucus composed of modified porous high iron ash, modified activated carbon and colloidal suspension in a weight ratio of 2-4:1-3:3-5.
3. A desulfurization, denitrification and dust removal process for low-sulfur flue gas according to claim 2, characterized in that: The granulation method is as follows: the mixed mucus is granulated by a disc-type pelletizer and then placed in a muffle furnace, the temperature of the muffle furnace is increased to 450-500° C., and the mixture is heat-insulated and roasted for 2-3 hours to obtain a desulfurization and denitration adsorbent, the pelletizer speed is 25 r / min, and the pelletizing diameter is 8-12 mm.
4. A desulfurization, denitrification and dust removal process for low-sulfur flue gas according to claim 2, characterized in that: The modified porous high iron ash is obtained by processing the following steps: A1. Add the fly ash crushed by ball mill and deionized water into a permanent magnetic wet separator for magnetic separation, and dry it in a drying oven at a temperature of 90-95° C. for 10-12 hours to obtain high iron ash; A2. Put high iron ash, calcium oxide and deionized water into a water bath, stir, filter and dry the filter cake in a vacuum drying oven at 90-110°C to constant weight to obtain high iron ash aggregate; A3. Add high iron ash aggregate and colloidal suspension into a reaction kettle, stir until slurry, place into a muffle furnace, raise the temperature of the muffle furnace to 400-600°C, keep warm and roast for 2-3h to obtain porous high iron ash; A4. Place the porous high iron ash and the modified solution into a cold water bath and stir, wash with deionized water until neutral, filter, and dry the filter cake in an empty drying oven at a temperature of 85-95°C for 10-12 hours to obtain modified porous high iron ash.
5. A desulfurization, denitrification and dust removal process for low-sulfur flue gas according to claim 4, characterized in that: In step A1, the fly ash and deionized water usage ratio is 100 g:20 mL, the ball mill speed is 500 r / min, the ball milling time is 4 h, and the permanent magnet magnetic field strength is 12000 GS.
6. A desulfurization, denitrification and dust removal process for low-sulfur flue gas according to claim 4, characterized in that: In step A2, the water bath temperature is 85-95° C., the stirring time is 3-5 h, and the amount ratio of high iron ash, calcium oxide, and deionized water is 3-5 g: 1-2 g: 250-270 mL.
7. A desulfurization, denitrification and dust removal process for low-sulfur flue gas according to claim 4, characterized in that: In step A3, the colloidal suspension is composed of sawdust pore-forming agent, sodium-based bentonite binder, and deionized water in a dosage ratio of 5-10g:30-40g:10-50mL, and the dosage ratio of iron ash aggregate and colloidal suspension is 40-50g:100-150mL.
8. A desulfurization, denitrification and dust removal process for low-sulfur flue gas according to claim 4, characterized in that: In step A4, the modified solution is composed of potassium hydroxide, sodium hypochlorite and deionized water in a ratio of 25-30g:10-15g:100-120mL, and the porous high iron ash and modified solution in a ratio of 10-12g:20-40mL.
9. A desulfurization, denitrification and dust removal process for low-sulfur flue gas according to claim 2, characterized in that: The modified activated carbon is obtained by processing the following steps: B1. Wash the coconut shell activated carbon with deionized water until it is neutral, dry it in a vacuum drying oven at a temperature of 100-110° C. to constant weight, and grind and screen 100-120 mesh activated carbon to obtain pretreated activated carbon; B2. Add the pretreated activated carbon and sodium hydroxide powder into a nickel boat, place the nickel boat into a nitrogen-protected tubular furnace, increase the temperature to 500-600° C., keep the temperature for 40-70 min, and obtain modified activated carbon by post-treatment.
10. A desulfurization, denitrification and dust removal process for low-sulfur flue gas according to claim 9, characterized in that: In step B2, the ratio of activated carbon to sodium hydroxide is 1g:1-5g, the flow rate of the tubular furnace is 200mL / min, and the heating rate is 5°C / min; post-treatment includes: cooling after the reaction is completed, adding hydrochloric acid to adjust the pH of the system to 5, maintaining for 30min, washing with deionized water, filtering, and drying the filter cake in a vacuum drying oven at a temperature of 100-110°C for 2-3h to obtain modified activated carbon.